Value Co-Creation Process of Tonnamtapi Handmade Community Enterprise by Art and Design Activities with Community Participation - Sathaporn, Chalaem; Tonkhundum, Passakorn; Tippaya, Tamisa; Linma, Thawatchai; Rodjaroen, Somrak; Theerachun, Sanatcha (Area Based Development Research Journal, 2021)
Tonnamtapi handmade community enterprise, Phipun district, Nakhon Si Thammarat province, gathered local people to produce chemical tie-dye products. However, their patterns lacked unique identities and were not well known, so that they could not generate high income. This research aimed to create the value of natural tie-dye products by art and design activities with community participation. Art and design were created for developing the knowledge and creative skills of this group of people. Then, they were integrated with community members’ skills to develop new tie-die patterns and new processed goods. The processes were as follows: 1) ) transferring art and design knowledge and creative workshop training, 2) art and design activities with community participation, 3) work development from art and design activities with community participation, 4) selection and evaluation of the community artwork and design, 5) presentation of artwork and design by organizing the art and design activities with community and network participation, evaluation of activity organization, search for distribution channels of community products, and 6) technology transfer to other community entrepreneurs and relevant agencies in Phipun district. The research caused the community enterprise to develop its unique patterns with its own community identities which were "twisting flow of Tapi River and Tapi upstream. The results were the community’s knowledge, designed packaging and tags, substitution of chemical color with natural color, reduction of the environmental problems, and production of processed clothes. Besides, the knowledge and skills of making tie-dye products were transferred to local people both in and out of the community. Furthermore, management of the activities of the Community Enterprise and career building generated the circular economy within the community. Total income were approximately 165,385 baht, which was increasing by 142.5%. Batik tie-dye products received the Community Product Standards, 4-Star OTOP Product, environmental standards. These outputs caused the extensions in terms of economic, social contribution, and public policy making in the local developing plan of Phipun district.